THE DEVELOPMENT OF AN ADDITIONAL COURSE ON THAI DRAMATIC ART SKILLS FOR GRADE 7 STUDENTS IN THE SECONDARY EDUCATIONAL SERVICE AREA OFFICE KALASIN - Paorisankhunnakorn, Jiranattakorn; Wongsaphan, Montri (Journal of MCU Social Science Review, 2024)
The purpose of this study was to develop an additional course of Thai dramatic art skills for grade 7 students under the Secondary Educational Service Area Office Kalasin. The samples were grade 7 students of Anukoolnaree School for 42 students. The research instruments were a knowledge test, and questionnaire. The data were analyzed by the use of mean, percentage, standard deviation, and compared by t-test (Dependent Samples). The findings were revealed as follows: The course comprised of principles, objectives, contents, learning activities, and assessments. There were five stages of learning integrated with practice skill and appreciation of Thai culture: 1. Preparation, 2. Practice, 3. Performance, 4. Design, and 5. Evaluation and Revision. The effectiveness of the course had an efficiency of 87.23/88.45. After implementing the course, it was found that its materials were consistent and valid. The results of evaluation on Thai dramatic art skill showed that the post-test mean score was higher than the pre-test mean score. The basic Thai dramatic art ability and the creative Thai dramatic art designing ability were at the highest levels and was statistically significant level at 0.05.